Central European Strigeidae Railliet, 1919 (Trematoda: Strigeidida): Molecular and comparative morphological analysis suggests the reclassification of Parastrigea robusta Szidat, 1928 into Strigea Abildgaard, 1790 - Heneberg, Petr; Sitko, Jiljí; Těšínský, Miroslav; Rząd, Izabella; Bizos, Jiří (Parasitology international, 2018)
Strigeidae Railliet, 1919 are digenean parasites of birds and mammals that are characteristic by their cup-shaped forebody and bilobed holdfast organ. Despite that the family is taxonomically unsettled, particularly due to a very limited number of visible autapomorphic identification features, molecular phylogenetics have never been applied to analyze the relationships among European members of Strigeidae except for the genus Ichthyocotylurus. Here, we analyze the Strigeidae found during the examination of Czech birds performed from 1962 to 2017, and we provide comparative measurements and host spectra, including prevalence and intensity; we also provide and analyze sequences of four DNA loci of 12 of the Strigeidae species. We suggest the reclassification of Parastrigea robusta Szidat, 1928 as Strigea robusta (Szidat, 1928) Heneberg and Sitko, 2018 comb. n. The genera Strigea Abildgaard, 1790 and Parastrigea Szidat, 1928 appear paraphyletic, and morphological diagnostic features of genera within Strigeini Dubois, 1936 are invalid. The mute swan Cygnus olor hosts two Cotylurus spp., Cotylurus syrius Dubois, 1934 and a second species with molecular identification features shared in part with Cotylurus cornutus (Rudolphi, 1808) and Cotylurus gallinulae Lutz, 1928. New host records are provided for seven species. Analyses of non-European genera of the Strigeidae are needed to provide an updated key to Strigeini.
Keywords: protozoální DNA; Aquila pomarina; Paraphyletic genus; fylogeneze; Strigiformes; Falconiformes; Česká republika; Sequence Analysis, DNA; Phylogeny; sekvenční analýza DNA; Birds of prey; prevalence; infekce červy třídy Trematoda; protozoální proteiny; Parastrigea robusta; DNA, Protozoan; nemoci ptáků; Czech Republic; hostitelská specificita; ptáci; Birds; Animals; zvířata; Trematoda; Bird Diseases; Prevalence; Trematode Infections; Protozoan Proteins; Host Specificity